Consumers’ green purchase intention to visit green hotels: A value-belief-norm theory perspective - Wang, Cen-Peng; Zhang, Qi; Wong, Philip Pong Weng; Wang, Lei (Frontiers in Psychology, 2023)
Introduction The theory of planned behavior (TPB) has dominated the limited number of green hotel visitation studies; however, those studies’ findings are often inconclusive or even controversial. Thus, research needs to move beyond using the TPB to measure consumers’ intention and behavior, and to experiment with alternative theoretical frameworks to explain behavioral change. Value-belief-norm theory of environmentalism (VBN) proposed that various facets of values can influence individuals’ beliefs, subsequently effecting their moral obligations, ultimately, their pro-environmental behaviors. Hence, this study aims to examine the relationship between value components (i.e., biospheric, altruistic, collectivistic), beliefs (i.e., explicit and implicit attitude), norms (i.e., social and personal norm), and green purchase intention to visit green hotels. Methods An online survey of convenience sampling technique was adopted for data collection. A total of 373 valid questionnaires were subjected to descriptive analysis, and confirmatory factor analysis and structural equation modeling were performed for the testing of the hypotheses. Results The results suggested that biospheric and collectivistic value positively influence explicit environmental attitude while altruistic value positively influences intrinsic environmental attitude, but negatively influences extrinsic environmental attitude. Social norm was shown to have a positive impact on personal norm and green purchase intention. Furthermore, implicit environmental attitude was shown to influence personal norm and intention, while personal norm positively influences green purchase intention to visit green hotels. Discussion This study provided an alternative perspective on the selection of green hotels among consumers based on value-belief-norm theory in the tourism literature. These empirical findings would greatly benefit green hotel managers and other key stakeholders in the hospitality industry.